Summary of the R&D of 20-inch MCP-PMTs for neutrino detection. (18th November 2021) - Wu, Q.; Qian, S.; Cao, Y.; Huang, G.; Jin, M.; Jin, Z.; Li, D.; Liu, H.; Li, K.; Liu, S.; Ma, L.; Ren, L.; et al.
Abstract: The Jiangmen Underground Neutrino Observatory (JUNO) in China aiming to determine the neutrino mass hierarchy is under construction. A new kind of large area microchannel-plate photomultiplier tube (MCP-PMT) was put forward for the JUNO by the researchers in Institute of High Energy Physics (IHEP) in China. After breaking through several core technotical barriers, the 20-inch MCP-PMT prototype with great performance was successfully produced by the MCP-PMT group in China and got 75% PMT orders (15, 000 pics) from JUNO. The mass production line and batch test system was completed in North Night Vision Technology Co., Ltd. (NNVT). The performance of the MCP-PMT including the gain, the quantum efficiency, the P / V ratio, the dark count rate and the transit time spread can be batch tested. During the mass production process, the technical progress in the cathode deposition method improved the quantum efficiency of the photocathode from 30% to 35%. The aging behaviour, temperature effect, the after-pulse distribution and the flash signal of the 20-inch MCP-PMT are all detailly studied. By August of 2020, the 15, 000 MCP-PMTs, which will be installed as the central liquid scintillator detector of JUNO, have been completed and delivered to Jiangmen. The average QE at 400 nm for the 15, 000 pieces of MCP-PMTs is 32%.